Development of Interactive Wordwall Games Based on Inquiry into Children's Mathematical Abilities in Kindergarten - Mellie Guspita Yanty; Rakimahwati; Farida Mayar; Yaswinda (Jurnal Penelitian Pendidikan IPA, 2026)
This study was conducted in response to the limited development of early childhood mathematical abilities, which is closely associated with the insufficient use of interactive and explorative learning media. The present research focuses on designing and evaluating an inquiry-oriented interactive wordwall game intended to enhance young children's mathematical competencies. The study employed a Research and Development framework using the ADDIE model, encompassing analysis, design, development, implementation, and evaluation phases. The participants involved 15 kindergarten children aged 5–6 years, while data were collected through expert validation, observation, questionnaires, and pre-test and post-test assessments. The findings reveal that the developed media achieved a very high level of feasibility, indicated by media and material validation scores of 96% and 92%, respectively. Practicality testing also demonstrated a very positive response from teachers and strong engagement from children. In terms of effectiveness, there was a substantial improvement in mathematical ability, reflected by an increase in average scores from 60.1% to 97%, with an N-Gain score of 0.91 categorized as high. These results suggest that combining interactive digital media with an inquiry-based approach can meaningfully support children's conceptual understanding and engagement. Therefore, the developed Wordwall-based learning media can be considered an effective and innovative tool for improving early childhood mathematics learning.